# Asymptotics of an integral depending on a parameter

Given the integral $$\int_{1}^{+\infty}\frac{1}{(1+a^2+x^2)^{\frac{\rho}{2}}(1+2\sqrt{E}x)}dx$$, with $$a,E>0$$ and $$\rho>2$$, I want to know how to determine how it goes to 0 as $$a\to +\infty$$. Maybe the answer is trivial, but I prefer being cautious

• Do you mean $\sqrt Ex$ or $\sqrt{Ex}$ ? – Yves Daoust Mar 26 '20 at 13:10
• Root only on $E$ – SpuriousMatemagician Mar 27 '20 at 18:01
• In such cases, don't clutter with a constant like $2\sqrt E$. $b$ is good enough. – Yves Daoust Mar 27 '20 at 19:37

## 2 Answers

I'll write $$b=2\sqrt E$$ to simplify things.

To get a systematic expansion, write

$$\begin{eqnarray} \int_1^a\frac1{(1+a^2+x^2)^\frac\rho2(1+bx)}\,\mathrm dx &=& \frac1{a^\rho b}\int_1^a\frac1{(1+\frac{x^2+1}{a^2})^\frac\rho2(1+\frac1{bx})x}\,\mathrm dx \\ &=& \frac1{a^\rho b}\int_1^a\sum_{j=0}^\infty\sum_{k=0}^\infty\binom{-\frac\rho 2}j\left(\frac{x^2+1}{a^2}\right)^j\left(-\frac1{bx}\right)^k\frac1x\,\mathrm dx \\ &=& \sum_{j=0}^\infty\sum_{k=0}^\infty\sum_{n=0}^j\frac{(-1)^k}{a^{\rho+2j}b^{k+1}}\binom{-\frac\rho 2}j\binom jn\int_1^ax^{2n-k-1}\,\mathrm dx\;. \\ &=& \sum_{j=0}^\infty\sum_{k=0}^\infty\sum_{n=0}^j\frac{(-1)^k}{a^{\rho+2j}b^{k+1}}\binom{-\frac\rho 2}j\binom jn \begin{cases} \ln a&2n-k=0\;,\\ \frac{a^{2n-k}-1}{2n-k}&\text{otherwise}\;. \end{cases} \end{eqnarray}$$

The leading term is the one for $$j=k=0$$, which yields

$$\frac{\ln a}{a^\rho b}\;,$$

as in @stokes-line’s answer. The next term comes from contributions for $$k=0$$, $$n=j\gt0$$:

$$\sum_{j=1}^\infty\frac1{a^{\rho+2j}b}\binom{-\frac\rho 2}j\frac{a^{2j}}{2j} = -\frac1{a^\rho b}\frac\rho4\,_3F_2\left(1,1,\frac\rho2+1;2,2;-1\right)\;,$$

where $$_3F_2$$ is a generalized hypergeometric series, and for $$j=0$$, $$k\gt0$$:

$$\sum_{k=1}^\infty\frac{(-1)^k}{a^\rho b^{k+1}}\frac{-1}{-k} = -\frac{\ln\left(1+\frac1b\right)}{a^\rho b}\;.$$

The term after that comes from $$k=1$$, $$n=j$$:

$$-\sum_{j=0}^\infty\frac1{a^{\rho+2j}b^2}\binom{-\frac\rho2} j\frac{a^{2j-1}}{2j-1} = \frac1{a^{\rho+1}b^2}\,_2F_1\left(-\frac12,\frac\rho2;\frac12;-1\right)\;.$$

For the part beyond $$a$$, we need to expand in $$\frac1x$$ instead, yielding

$$\begin{eqnarray} \int_a^\infty\frac1{(1+a^2+x^2)^\frac\rho2(1+bx)}\,\mathrm dx &=& \int_a^\infty\frac1{bx^{\rho+1}}\frac1{\left(1+\frac{a^2+1}{x^2}\right)^\frac\rho2\left(1+\frac1{bx}\right)}\,\mathrm dx \\ &=& \int_a^\infty\frac1{bx^{\rho+1}}\sum_{j=0}^\infty\sum_{k=0}^\infty\binom{-\frac\rho2}j\left(\frac{a^2+1}{x^2}\right)^j\left(-\frac1{bx}\right)^k\,\mathrm dx \\ &=& \sum_{j=0}^\infty\sum_{k=0}^\infty\binom{-\frac\rho2}j\frac{(-1)^k}{a^{\rho+2j+k}b^{k+1}}(a^2+1)^j\int_1^\infty t^{-(\rho+2j+k+1)}\,\mathrm dt \\ &=& \sum_{j=0}^\infty\sum_{k=0}^\infty\sum_{n=0}^j\binom{-\frac\rho2}j\binom jn\frac{(-1)^k}{a^{\rho+2j+k-2n}b^{k+1}}\frac1{\rho+2j+k}\;. \end{eqnarray}$$

Here there is no logarithmic term; the first term comes from $$k=0$$, $$n=j$$:

$$\sum_{j=0}^\infty\binom{-\frac\rho2}j\frac1{a^\rho b}\frac1{\rho+2j}=\frac1{a^\rho b}\frac1\rho\,_2F_1\left(\frac\rho2,\frac\rho2;\frac\rho2+1;-1\right)\;.$$

The next term comes from $$k=1$$, $$n=j$$:

$$-\sum_{j=0}^\infty\binom{-\frac\rho2}j\frac1{a^{\rho+1}b^2}\frac1{\rho+2j+1}=-\frac1{a^{\rho+1}b^2}\frac1{\rho+1}\,_2F_1\left(\frac\rho2,\frac{\rho+1}2;\frac{\rho+3}2;-1\right)\;.$$

Thus, altogether we have the expansion

$$\int_1^a\frac1{(1+a^2+x^2)^\frac\rho2(1+bx)}\,\mathrm dx \\ = \frac{\ln a-\ln\left(1+\frac1b\right)}{a^\rho b} + \left(\frac1\rho\,_2F_1\left(\frac\rho2,\frac\rho2;\frac\rho2+1;-1\right)-\frac\rho4\,_3F_2\left(1,1,\frac\rho2+1;2,2;-1\right)\right)\frac1{a^\rho b} \\ +\left(_2F_1\left(-\frac12,\frac\rho2;\frac12;-1\right)-\frac1{\rho+1}\,_2F_1\left(\frac\rho2,\frac{\rho+1}2;\frac{\rho+3}2;-1\right)\right)\frac1{a^{\rho+1}b^2} \\ +O\left(\frac1{a^{\rho+2}}\right)\;.$$

For integer values of $$\rho$$, the hypergeometric series yield simple expressions. For instance, for $$\rho=2$$ the expansion takes the form

$$\int_1^a\frac1{(1+a^2+x^2)(1+bx)}\,\mathrm dx \\ = \frac{\ln a-\ln\left(1+\frac1b\right)}{a^2 b} + \left(\frac12\,_2F_1\left(1,1;2;-1\right)-\frac12\,_3F_2\left(1,1,2;2,2;-1\right)\right)\frac1{a^2 b} \\ +\left(_2F_1\left(-\frac12,1;\frac12;-1\right)-\frac13\,_2F_1\left(2,\frac32;\frac52;-1\right)\right)\frac1{a^3b^2} \\ +O\left(\frac1{a^4}\right)\;. \\ = \frac{\ln a-\ln\left(1+\frac1b\right)}{a^2 b} +\frac{\frac54+\frac\pi8}{a^3b^2} +O\left(\frac1{a^4}\right)\;.$$

The terms proportional to $$\frac1{a^2b}$$ cancel. For $$\rho=3$$, the result is

$$\int_1^a\frac1{(1+a^2+x^2)^\frac32(1+bx)}\,\mathrm dx \\ = \frac{\ln a-\ln\left(1+\frac1b\right)}{a^3 b} + \left(\frac13\,_2F_1\left(\frac32,\frac32;\frac52;-1\right)-\frac34\,_3F_2\left(1,1,\frac52;2,2;-1\right)\right)\frac1{a^3 b} \\ +\left(_2F_1\left(-\frac12,\frac32;\frac12;-1\right)-\frac14\,_2F_1\left(\frac32,2;3;-1\right)\right)\frac1{a^4b^2} \\ +O\left(\frac1{a^5}\right)\;. \\ = \frac{\ln a-\ln\left(1+\frac1b\right)}{a^3 b} +\frac{\ln2-1}{a^3 b} +\frac2{a^4b^2} +O\left(\frac1{a^5}\right)\;.$$

For $$\rho=4$$, the result is

$$\int_1^a\frac1{(1+a^2+x^2)^2(1+bx)}\,\mathrm dx \\ = \frac{\ln a-\ln\left(1+\frac1b\right)}{a^4 b} + \left(\frac14\,_2F_1\left(2,2;3;-1\right)-\,_3F_2\left(1,1,3;2,2;-1\right)\right)\frac1{a^4 b} \\ +\left(_2F_1\left(-\frac12,2;\frac12;-1\right)-\frac15\,_2F_1\left(2,\frac52;\frac72;-1\right)\right)\frac1{a^5b^2} \\ +O\left(\frac1{a^6}\right)\;. \\ = \frac{\ln a-\ln\left(1+\frac1b\right)}{a^4 b} -{\frac12}\frac1{a^4 b} +\frac{3\pi}4\frac1{a^5b^2} +O\left(\frac1{a^6}\right)\;.$$

For $$\rho=5$$, the result is

$$\int_1^a\frac1{(1+a^2+x^2)^\frac52(1+bx)}\,\mathrm dx \\ = \frac{\ln a-\ln\left(1+\frac1b\right)}{a^5 b} + \left(\frac14\,_2F_1\left(\frac52,\frac52;\frac72;-1\right)-\,_3F_2\left(1,1,\frac72;2,2;-1\right)\right)\frac1{a^5 b} \\ +\left(_2F_1\left(-\frac12,\frac52;\frac12;-1\right)-\frac15\,_2F_1\left(\frac52,3;4;-1\right)\right)\frac1{a^6b^2} \\ +O\left(\frac1{a^7}\right)\;. \\ = \frac{\ln a-\ln\left(1+\frac1b\right)}{a^5 b} +\frac{\ln2-\frac43}{a^5 b} +\frac83\frac1{a^6b^2} +O\left(\frac1{a^7}\right)\;.$$

• Thank you so much for this very detailed answer. I am interested only in the leading term, and this helped me understand the way it is computed. Instead, I didn't get why the next term comes from $k=0, n=j>0$ – SpuriousMatemagician Mar 27 '20 at 18:12
• @SpuriousMatemagician: That's only the first part of the sentence; the next term comes from contributions from $k=0$, $n=j\gt0$ and from $j=0$, $k\gt0$. If you look at the powers of $a$ in the triple summation, there's $a^{\rho+2j}$ in the denominator, and the integration yields a term with $a^{2n-k}$ and a constant term. – joriki Mar 27 '20 at 18:21
• Since $j$, $k$ and $n$ are all non-negative, for these exponents to add up to $a^\rho$ in the denominator, we must have $k=0$ and $n=j$ in the term $a^{2n-k}$ (and then $j\gt0$ because $k=j=0$ is the leading logarithmic term), or $j=0$ in the constant term (and then $k\gt0$ because $k=j=0$ is the leading logarithmic term). (And then of course there's a third contribution of order $a^{-\rho}$ that comes from the part of the integral beyond $a$.) – joriki Mar 27 '20 at 18:21
• Ok. One more thing: let's say i am interested only in the leading term, When considering the part beyond $a$, after i have the series rapresentation, I can discard this part when related to the one below $a$, because here I have no logarithmic terms, right? – SpuriousMatemagician Mar 28 '20 at 3:03

The leading asymptotics can be found realizing that at large $$a$$ the integral comes from $$1\lesssim x\lesssim a$$ and is logarithmic in this range. As a result: $$I\sim \frac{\ln a}{2 \sqrt{E} a^\rho}.$$

• Can you go a little deeper in explaining this? If i gor it right, I have to split the integral in two parts: in $[1,a]$ and in $[a,+\infty]$. But then? Maybe in the first I can take out $a^2$ and write the Taylor expansion? Anyway i am not sure on how to proceed – SpuriousMatemagician Mar 25 '20 at 21:38
• It depends on what accuracy you want. Thats the leading term, to get it you need to observe that the integrand quickly decays at $x>a$ and for $1\lesssim x \lesssim a$ you need to keep dependence on $x$ only in the second term in the denominator. The rest gives subleading corrections. – stokes-line Mar 25 '20 at 21:52